MENGEMBANGKAN PEMBELAJARAN SASTRA DI SD - Ramadani, Cintia Aulia; Hamzah, Rahma Ashari (Pascasarjana, Universitas Negeri Gorontalo, 2025)
Literature learning in elementary schools plays a strategic role in developing students' character and literacy competencies. However, various challenges such as limited teacher competencies, shortage of quality teaching materials, and low reading interest hinder optimal learning outcomes. This study aims to develop a comprehensive framework for literature learning in elementary schools by examining its essential components including learning objectives, student characteristics, teacher roles, content materials, methods, media, and evaluation mechanisms. This research employs a library research method involving critical examination of academic books, scientific journals, official educational policy documents, and previous research reports. The analysis reveals that effective literature learning must be based on principles of developmental appropriateness, meaningfulness, integration, active participation, creativity, appreciation, and contextuality. The findings indicate that literature learning development requires multi-dimensional approaches including enhancing teacher competencies through continuous professional development, providing diverse quality teaching materials, implementing comprehensive literacy programs, utilizing innovative student-centered learning strategies, developing authentic assessments, and leveraging digital technology. This study contributes to providing theoretical foundations and practical guidelines for educators in designing more effective and meaningful literature learning in elementary schools.